The Influence Of Organizational Dynamics, Quality Of Life, And Motivation For Achievement On Commitment And Work Behavior at XYZ Hospital - Ayung Wandira Machsa; Vera Firdaus; Rita Ambarwati Sukmono (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the influence of organizational dynamics, quality of life, and achievement motivation on employee commitment and work behavior at XYZ Hospital, Sidaorjo. The type of research conducted by the author in this study is quantitative descriptive research, in quantitative descriptive research, the sampling technique used is the purposive sampling technique in data collection. The location of the research conducted by the author to test the hypothesis is at XYZ Hospital located in Sidoarjo, East Java. The number of respondents in this study is assumed to be 100 respondents. The data analysis techniques used were multiple linear regression analysis, t-test, and f-test. The results of this analysis not only provide statistical significance values but also parameter estimation that explains the strength of the relationship between variables.